Association of copy number polymorphisms at the promoter and translated region of COMT with Japanese patients with schizophrenia. Issue 3 (7th February 2016) - Higashiyama, Ryoko; Ohnuma, Tohru; Takebayashi, Yuto; Hanzawa, Ryo; Shibata, Nobuto; Yamamori, Hidenaga; Yasuda, Yuka; Kushima, Itaru; Aleksic, Branko; Kondo, Kenji; Ikeda, Masashi; Hashimoto, Ryota; et al.
Abstract : Chromosome 22q11.2 deletion syndrome and genetic variations including single‐nucleotide polymorphism (SNP) and copy number variation (CNV) in catechol‐O‐methyltransferase ( COMT ) situated at 22q11.2 remains controversial. Here, the genetic relationship between COMT and Japanese patients with schizophrenia was investigated by examining whether the SNPs correlated with schizophrenia based on a common disease–common variant hypothesis. Additionally, 22q11.2DS were screened based on a common disease–rare variant hypothesis; low‐frequency CNVs situated at two COMT promoters and exons were investigated based on the low‐frequency variants with an intermediate effect; and positive findings from the first stage were reconfirmed using a second‐stage replication study including a larger sample size. Eight SNPs and 10 CNVs were investigated using Taqman SNP and CNV quantitative real‐time polymerase chain reaction method. For the first‐stage analysis, 513 unrelated Japanese patients with schizophrenia and 705 healthy controls were examined. For the second‐stage replication study, positive findings from the first stage were further investigated using a larger sample size, namely 1, 854 patients with schizophrenia and 2, 137 controls. The first‐stage analysis showed significant associations among schizophrenia, intronic SNP rs165774, CNV6 situated at promoter 1, CNV8 at exon 6, and CNV9 at exon 7. The second‐stage study showed that intronic SNP rs165774 (χ 2 = 8.327, P = 0.0039), CNV6 (χ 2 = 19.66, P = 0.00005), and CNV8 (χ 2 = 16.57, P = 0.00025) were significantly associated with schizophrenia. Large and rare CNVs as well as low‐frequency CNVs and relatively small CNVs, namely <30 kb in COMT, may be genetic risk factors for schizophrenia. © 2016 Wiley Periodicals, Inc.